2020
DOI: 10.3390/cancers12071783
|View full text |Cite
|
Sign up to set email alerts
|

Elective Neck Dissection or Sentinel Lymph Node Biopsy in Early Stage Oral Cavity Cancer Patients: The Dutch Experience

Abstract: Background: Sentinel lymph node biopsy (SLNB) has been introduced as a diagnostic staging modality for detection of occult metastases in patients with early stage oral cancer. Comparisons regarding accuracy to the routinely used elective neck dissection (END) are lacking in literature. Methods: A retrospective, multicenter cohort study included 390 patients staged by END and 488 by SLNB. Results: The overall sensitivity (84% vs. 81%, p = 0.612) and negative predictive value (NPV) (93%, p = 1.000) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
54
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 46 publications
(60 reference statements)
3
54
1
Order By: Relevance
“…However, the diagnosis of small cervical LNs for evaluating the nodal status using 18F-FDG PET is limited, owing to false-negative findings [ 7 , 8 ]. Additionally, the sensitivity of sentinel LN biopsy and sentinel LN imaging techniques using CT or MR lymphography and PET lymphoscintigraphy is 56–91% [ 9 , 10 ]. Unfortunately, metastatic cervical LNs are not easily detected on a pretreatment clinical examination.…”
Section: Introductionmentioning
confidence: 99%
“…However, the diagnosis of small cervical LNs for evaluating the nodal status using 18F-FDG PET is limited, owing to false-negative findings [ 7 , 8 ]. Additionally, the sensitivity of sentinel LN biopsy and sentinel LN imaging techniques using CT or MR lymphography and PET lymphoscintigraphy is 56–91% [ 9 , 10 ]. Unfortunately, metastatic cervical LNs are not easily detected on a pretreatment clinical examination.…”
Section: Introductionmentioning
confidence: 99%
“…5 A recent retrospective, multicenter study that included 390 patients staged by END and 488 patients staged by SLNB found comparable overall sensitivity (84% vs 81%) and negative predictive value (NPV) (both 93%), also when stratified for pathological primary tumor (T) stages. 6 In the French Senti-MER trial, the only randomized controlled clinical trial, 307 patients with cT1-2N0 were randomly assigned between END and SNLB. Recurrence-free, locoregional-free, disease-specific, and overall survival were not different for either group.…”
mentioning
confidence: 99%
“…Sentinel lymph node biopsy (SLNB) has been implemented in most Dutch Head and Neck Cancer institutions as a standard oncological care for staging the clinically negative neck in early-stage (cT1/2N0) oral squamous cell carcinoma (OSCC) [1]. As SLNB has shown to accurately stage the clinically negative neck in these patients, with a pooled sensitivity of 87% and negative predictive value of 94%, SLNB offers a reliable, less invasive alternative for elective neck dissection with overall lower morbidity rates, better qualityof-life, and lower healthcare costs [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…Especially in cases where sentinel lymph nodes (SLNs) are located in proximity of the primary tumor, the activity residing at the radiotracer injection site can conceal these adjacent SLNs and impede distinction between SLN and injection site. This so-called shine-through phenomenon is notably manifest in floor-ofmouth OSCC, resulting in a significant lower accuracy of SLNB in floor-of-mouth tumors (sensitivity 63%; NPV 90%) compared to other OSCC subsites (sensitivity 86%; NPV 95%) [1]. Such decline in diagnostic accuracy increases the risk of neglecting occult lymph node metastasis that will inevitably develop into clinical manifestation of disease and consequently induce a poor oncological prognosis [11,12].…”
mentioning
confidence: 99%